A catalog of emission-line galaxies from the Faint Infrared Grism Survey: studying environmental influence on star formation - Pharo, John; Malhotra, Sangeeta; Rhoads, James E.; Pirzkal, Norbert; Finkelstein, Steven L.; Ryan, Russell; Cimatti, Andrea; Christensen, Lise; Hathi, Nimish; Koekemoer, Anton; Harish, Santosh; Smith, Mark; et al. (The astrophysical journal, 2020)
We present a catalog of 208 0.3 28 and >10−17 erg cm−2 s−1 line flux. We use the resulting line catalog to investigate a possible relationship between line emission and a galaxy’s environment. We use seventh-nearest-neighbor distances to investigate the typical surroundings of ELGs compared to non-ELGs, and we find that [O iii] emitters are preferentially found at intermediate galaxy densities near galaxy groups. We characterize these ELGs in terms of the galaxy specific star formation rate (SFR) versus stellar mass and find no significant influence of environment on that relation. We calculate SFRs and find no dependence of SFR on local galaxy surface density for 0.3 < z < 0.8 Hα emitters and for 0.8 < z < 1.3 [O iii] emitters. We find similar rates of close-pair interaction between ELGs and non-ELGs. For galaxy surface densities Σ ≤ 30 Mpc−2, we find no consistent effect of environment on star formation.